ChemInform Abstract: Arylcalcium Halides as Substrates in Kumada‐Type Cross‐Coupling Reactions. Issue 30 (29th July 2014) - Langer, Jens; Koehler, Mathias; Goerls, Helmar; Westerhausen, Matthias
Abstract Ni‐catalyzed cross‐coupling reactions of arylcalcium iodides with aryl chlorides provide biphenyls in moderate yields.